CYTOKININS: DISTRIBUTION IN SPECIES OF YEAST TRANSFER RNA - Armstrong, D. J. (1969)
Transfer RNA fractions from Saccharomyces lactis and Saccharomyces cerevisiae have been tested for cytokinin activity in the tobacco bioassay. Cysteine tRNA has been identified as a cytokinin-containing tRNA species in S. cerevisiae. Acid hydrolysates of S. lactis tRNA fractions (containing arginine tryptophan, and valine acceptor activities) and S. cerevisiae tRNA fractions (containing alanine, asparagine, aspartic acid, glutamic acid, glycine, histidine, tryptophan, and valine acceptor activities) were inactive in the tobacco bioassay. Cytokinins have been found only in those tRNA species corresponding to codons beginning with U.